The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00005537-199903000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and hypertonic saline solutions impair ciliary activity in vitro

Abstract: LR is an isotonic solution that has no effect on CBF. Therefore it is probable that this solution is more appropriate than saline for nasal irrigation and nebulization or antral lavage. Moreover, the results of this study suggest that mucolytic effects induced by hyperosmolarity should be attained preferably with hypertonic saline 7% in patients with cystic fibrosis or asthma. At this concentration, the ciliostatic effect is reversible, whereas irreversible changes are to be expected at higher concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 17 publications
3
78
1
11
Order By: Relevance
“…They concluded that 0.9% NaCI had moderate and temporary ciliostatic, that 7% NaCI exhibited complete but reversible effect and that 14.4% had a complete and irreversible effect, but that Ringer's solution had no such effect effects. They also emphasized that Ringer's solution closely approximates to extracellular fluid and has no adverse effect on ciliary beat frequency, for which reason it is more suitable that saline for antral lavage, nebulization and nasal irrigation [14].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that 0.9% NaCI had moderate and temporary ciliostatic, that 7% NaCI exhibited complete but reversible effect and that 14.4% had a complete and irreversible effect, but that Ringer's solution had no such effect effects. They also emphasized that Ringer's solution closely approximates to extracellular fluid and has no adverse effect on ciliary beat frequency, for which reason it is more suitable that saline for antral lavage, nebulization and nasal irrigation [14].…”
Section: Discussionmentioning
confidence: 99%
“…The best mucociliary clearance is attained with the inhalation of HSS at concentrations of between 3% and 12% with the effect dependent on the dose [9,10]. The tolerance limit is 12% as higher concentrations may cause pharyngeal irritation and at a concentration of 14.4% the ciliostatic effect is irreversible [10].…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto verifica-se que, apesar da hipertonicidade ser um fator que aparentemente atue de forma positiva, ela não deve ser muito acentuada, uma vez que alguns trabalhos publicados já demonstraram que soluções com alta hipertonicidade podem causar efeitos locais indesejáveis, como cilioestase reversível em mucosa de seio esfenóide após 5 min de exposição a solução salina a 7%, e cilioestase irreversível após exposição a solução a 14,4% 26 . Além da diminuição do batimento ciliar, também foi observada disjunção das células epiteliais in vitro, em fragmento submetidos a soluções salinas hipertônicas, a 3% e a 7% 28 .…”
Section: Discussionunclassified
“…Soluções contendo potássio, como a solução de Ringer com Lactato (que contém 0,030g de cloreto de potássio em 100ml de solução) e a solução de Locke Ringer (com 0,042g em 100ml) foram usadas em estudos envolvendo mucosa nasal e apresentaram resultados favoráveis 12,26,29 . Os resultados deste estudo sugerem que a presença deste íon não foi determinante de nenhuma das alterações encontradas na mucosa.…”
Section: Discussionunclassified